KONTRIBUSI TASAWUF BAGI PENGEMBANGAN PENDIDIKAN ISLAM - Wasehudin Wasehudin (IAIN Surakarta, 2018)
Futurologists, since the 20th century, have predicted that the Indonesian nation will carry out a process of secularization, which makes the role of religion increasingly dominant in decision making, both in the social, economic, political and cultural spheres. The dominance of science and technology will shift to religious considerations in decision making in social life. Islamic education as a vehicle to teach that religion is a source of peace must make a transformative breakthrough, thus that Islamic values return to their basic framework. This article by philosophical study intends to trace the contribution of Sufism to Islamic education. It’s found that a conflict of understanding between the sharia and the essence of Sufism has resulted in a polytheism view. This happened because the inability to rationalize philosophical Sufism became mysticism. This inability to implicate the search for divine values only focuses on philosophical truth values, which leads to the dualism of truth between the sharia and the essence. In fact, these two paths of truth are integrated and united, thus contributing to the fortification of the formation of noble character in Islamic education.